Analisis Biaya Penyakit Diabetes Melitus Sebagai Pertimbangan Perencanaan Pembiayaan Kesehatan: Cost Analysis of Diabetes Mellitus Disease as Considerations In Health Funding Planning - Abror, Nurul Ambianti; Andayani, Tri Murti; Sulistiawaty, Endang (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2019)
Disease cost analysis is an important element in the decision making process of chronic disease, because it can evaluate the cost of illness and illustrate diseases that require an increase in resources for the prevention or therapy. This study aims to determine the total cost of diabetes mellitus (DM), so it can be used as a health fund planning considerations related to the effectiveness and efficiency of medication costs for patients in Yogyakarta Regional Public Hospital. The method used is observational prevalence. The data were obtained retrospectively with patients primary diagnosed and secondary diagnosed of diabetes mellitus with or without complications in the period January to June 2014 in Yogyakarta Regional Public Hospital. The Financial perspective used is the hospitals perspective as health care providers to take into account the direct medical costs by using a bottom-up approach. Data analysis was performed using Kruskal-Wallis and Mann-Whitney Whitney to determine differences in the direct medical costs of outpatient diabetic patients in terms of age, the number and type of diabetes complications, as well as to determine the direct medical cost differences hospitalized diabetic patients in terms of age, the number of complications, type of diabetes, duration of hospitalization and inpatient classes.The results of the research showed that the patients who entered the inclusion criteria as much as 1.689 episodes of visits, which consisted of 1.531 episodes of outpatients visits and 158 episodes of inpatients visits. The total cost of DM based on hospital perspective Rp1.203.799.389,00 IDR within six months. There is a significant difference in direct medical costs in outpatients in terms of the number of factors of complications (p=0.004) and a significant differences direct medical costs inpatients in terms of the number of factors of complications, length of stay and inpatient class in hospitalization (p=0.000).